Entrepreneurship and knowledge spillovers from the public sector - Audretsch, D.B (Springer New York LLC, 2019)
A compelling body of research has found that investments in knowledge from other firms and universities spill over to enhance the performance of entrepreneurial firms. This literature has shown that firm performance is positively related to investments in new knowledge by other firms and research universities. This paper addresses a gap in the literature by positing that public sector knowledge is also conducive to enhancing performance by knowledge intensive entrepreneurial (KIE) firms. Our findings suggest that the public sector provides a fertile source of knowledge for enhancing KIE firm performance. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.